Shock fabrics in fine‐grained micrometeorites. (24th July 2017) - Suttle, M. D.; Genge, M. J.; Russell, S. S.
Abstract: The orientations of dehydration cracks and fracture networks in fine‐grained, unmelted micrometeorites were analyzed using rose diagrams and entropy calculations. As cracks exploit pre‐existing anisotropies, analysis of their orientation provides a mechanism with which to study the subtle petrofabrics preserved within fine‐grained and amorphous materials. Both uniaxial and biaxial fabrics are discovered, often with a relatively wide spread in orientations (40°–60°). Brittle deformation cataclasis and rotated olivine grains are reported from a single micrometeorite. This paper provides the first evidence for impact‐induced shock deformation in fine‐grained micrometeorites. The presence of pervasive, low‐grade shock features in CM chondrites and CM‐like dust, anomalously low‐density measurements for C‐type asteroids, and impact experiments which suggest CM chondrites are highly prone to disruption all imply that CM parent bodies are unlikely to have remained intact and instead exist as a collection of loosely aggregated rubble‐pile asteroids, composed of primitive shocked clasts.